Microstructural and electrical properties of the sofc anode precursor YSZ/NiO composite prepared by A liquid mixture technique - Esposito, V. (2005)
A detailed study of the microstructural and electrical properties of the yttria-stabilized zirconia/nickel oxide (YSZ/NiO) composite was performed. This material is the precursor to the solid oxide fuel cell anode cermet YSZ/Ni. A liquid mixture technique was developed to produce the YSZ/NiO composite to fabricate high-performance SOFC anodes. This technique resulted in fine and homogeneous powders and specimens with high electrical conductivity. The combined results showed that this technique is suitable for the production of the anode cermet.